الثورة الصناعية الرابعة - بعضي, آسيا (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة الى التعرف الى الثورة الصناعية الرابعة مفهومها خصائصها تقنياتها الاساسية الفرص والتحديات التي تقدمها للعالم . ولقد توصلت الدراسة الى ان الثورة الصناعية الرابعة نتيجة التطور المتسارع للتكنولجيا وتطبيفاتها، سيكون لهذه الثورة العديد من المساهمات التي ستؤدي الى تحسين حودة الحياة، وزيادة معدلات النمو في مختلف مجالات ، تخفيض التكلفة وزيادة الكفاءة، كما تواجه تحديات مختلفة كعدم المساواة في سوق العمل، الامن السيبراني الفرصنة ، بالاضافة اى المخاوف من الحدود الاخلاقية للتطور التكنولوجي . The study aimed to identify the fourth industrial revolution, its concept, characteristics, basic technologies, opportunities and challenges that it presents to the world. The study concluded that the Fourth Industrial Revolution, as a result of the rapid development of technology and its applications, will have many contributions that will lead to improving the quality of life, increasing growth rates in various fields, reducing costs and increasing efficiency . It also faces various challenges such as inequality in the labor market, cyber security and opportunity, in addition to concerns about the ethical limits of technological development .
The Forth industrial revolution
مقال
Keywords: الثورة الصناعية الرابعة التقنيات الفرص ، التحديات